Library Use Instruction on Undergraduates’ Utilization of Library Resource - Esoswo Francisca Ogbomo (D3 Perpustakaan Fakultas Vokasi Universitas Airlangga, 2023)
Background of the study: This study investigated the effects of library use instruction on undergraduate utilization of library resources: a case study of the Delta State University Library, Abraka. Purpose: The study’s major goal is to investigate library use instruction and undergraduates’ utilization of library resources. Method: The descriptive survey research design was used in this study. The population of the study is 4,714 Faculty of Education students. A sample size of 256 was chosen for this study. A questionnaire was the instrument used to collect data from the respondents. Descriptive statistics (frequency) and the statistical mean were used to analyze the data. Findings: The study found that the types of library resources used by undergraduates are the internet, databases, computer software, e-books, and books. The extent to which they use library resources is low. The types of library use instruction taught to the students are library orientation and electronic databases. The extent to which they participate in the instruction is low. Conclusion: Consequently, the study recommended that the Delta State University Library make library use instruction programs mandatory for both freshmen and transfer students in order to improve their use of library resources.